The General Perception of Corporate Social Responsibility (CSR): Does Countries, Income Groups, Legal Traditions,Education Level Influent the Perception? - Teo, Elaine Khai Lin (2008)
With increasing awareness of corporate social responsibility (CSR), corporations are starting to include their corporate social responsibilities and performances into their annual report to publish their effort and make their commitment known to stakeholders (Wood, 1991). However, there is always a question on what the general perceptions on corporate social responsibilities, and how much companies should be held responsible for their activities. The objective of this dissertation is to investigate factors that influence the perceptions on corporate social responsibilities. This study uses data obtained from a questionnaire developed by Globescan. A subset of 15 questions was selected from the wider questionnaire in relation to the perception of responsibilities should be held by companies. The first part of the study shows that companies are expected to be held more responsible in ethical responsibilities compared to economical, legal and philanthropic responsibilities. The second part of the analysis reveals that different countries, countries income groups, legal traditions, and education level have significant differences on the expectation on companies’ responsibilities. However, there is one exception case, that different countries income groups has no significant different on the expectation on companies to ensure all materials they use to make their products have been produced in a socially and environmentally responsible.